Effect of parathyroid hormone on serum magnesium levels: the neglected relationship in hemodialysis patients with secondary hyperparathyroidism. (2nd January 2016) - Fang, Li; Tang, Bing; Hou, Dawei; Meng, Meijuan; Xiong, Mingxia; Yang, Junwei
Abstract: Chronic kidney disease–mineral and bone disorder (CKD–MBD) is an important complication in patients with end-stage renal disease. Since recent studies have shown that magnesium (Mg) disturbance plays an important role in CKD–MBD and cardiovascular mortality, the interest on magnesium has grown recently. Although much concern focused on the effect of Mg on parathyroid hormone (PTH) levels, however, the influence of PTH on serum Mg levels is nearly unexplored. To evaluate the effect of PTH on serum Mg levels, we first described the relationship between serum Mg and PTH in secondary hyperparathyroidism. Besides, we also monitored the changes of serum Mg concentration after parathyroidectomy (PTX) in 23 patients. In our study, we found that hypermagnesemia (>2.5 mg/dL) occurred in up to 44% of cases and hypomagnesemia did not present. No statistically signiﬁcant correlations were found between serum Mg levels and PTH ( r  = −0.143, p  = 0.134). Correlation analysis and regression analysis suggested that the derangement of magnesium homeostasis was consistent with the derangement of calcium/phosphorus homeostasis. However, after PTX, serum magnesium levels dropped immediately after the surgery, minimally at the first day and gradually restored from the third day. The changes of serum Mg after surgery was positive correlated with the changes of serum phosphate ( r  = 0.558, p  = 0.003). Taken altogether, our data suggested that the therapeutic strategies to achieve optimum serum magnesium levels in CKD-MBD should take into account the varying stages of disease development since PTH could also influence magnesium metabolism and this problem might be important in severe secondary hyperparathyroidism.